REVIEW PENGUJIAN HUKUM MALUS DAN SIFAT OPTIS AKTIF LARUTAN GULA MENGGUNAKAN SISTEM DETEKSI CAHAYA - Amitasari, Ria; Istiyawan, Wardono; Sugito, Heri; Bawono P, Ari; Firdausi, K Sofjan (BERKALA FISIKA, 2013)
Abstract In this paper, we review the test results of Malus’ Law and optical activity of sugarsolution using a system light detector. Two polarizers were used in the experiment to serve thechoice of a certain direction of electric field of light and to determine the change of polarizationangle. The change of transmitted intensity were measured using LDR detector which was thenacquisitioned by microcontroller and displayed via LCD and computer using  Microsoft Visual Studio C#. The experiment result is in agreement to the Malus’ Law with correlation coefficient of 0.99, and by using the equipment we obtain linearity between the change of polarization angle andconcentration of sugar solution, which is appropriate to the theory, as well. The specific rotarypower is (54±2) o/dm(g/mL) in the experimental uncertainty.Keywords: Malus law, change of polarization angle, light detector